Pengembangan Media Audio Visual Dalam Meningkatkan Pembelajaran PAI Kisah Nabi Muhammad SAW Membangun Kota Madinah Di SDN Oro-Oro Pule Kejayan Pasuruan - Muhammad Sofiyulloh; Ahmad Ma’ruf; Muhammada (4, 2024)
This study aims to develop audiovisual media in Islamic Religious Education (PAI) learning, specifically on the story of the Prophet Muhammad SAW building the City of Medina at SDN Oro-Oro Pule, Kejayan, Pasuruan. The background of the study is based on the needs of students for learning media that are interesting, interactive, and able to provide meaningful learning experiences. The history of the Prophet is often considered difficult to understand if only delivered verbally through the lecture method, so that media innovations are needed that can present stories visually and auditorily to make them easier for students to digest. This study uses a research and development method (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fifth-grade students of SDN Oro-Oro Pule. Data collection techniques were carried out through observation, interviews, questionnaires, and product trials. Data were analyzed descriptively qualitatively and quantitatively to determine the feasibility and effectiveness of the developed media. The results of the study indicate that the developed audiovisual media is considered very suitable for use in PAI learning, both in terms of material, appearance, and ease of use. Teacher and student responses indicated a high level of satisfaction, as this media fostered interest in learning, facilitated understanding of the Prophet's story, and increased student active participation in the learning process. Furthermore, the implementation of this media positively impacted learning outcomes, as evidenced by the increase in students' average grades after using the media. Thus, the development of audiovisual media has proven effective in improving the quality of Islamic Religious Education (PAI) learning, particularly in elementary schools, on the story of the Prophet Muhammad's construction of Medina. Abstrak Penelitian ini bertujuan untuk mengembangkan media audio visual dalam pembelajaran Pendidikan Agama Islam (PAI), khususnya pada materi kisah Nabi Muhammad SAW membangun Kota Madinah di SDN Oro-Oro Pule, Kejayan, Pasuruan. Latar belakang penelitian didasari oleh kebutuhan peserta didik terhadap media pembelajaran yang menarik, interaktif, dan mampu menghadirkan pengalaman belajar bermakna. Materi sejarah Nabi seringkali dianggap sulit dipahami jika hanya disampaikan secara verbal melalui metode ceramah, sehingga diperlukan inovasi media yang dapat menampilkan kisah secara visual dan auditori agar lebih mudah dicerna siswa. Penelitian ini menggunakan metode penelitian dan pengembangan (Research and Development) dengan model ADDIE (Analysis, Design, Development, Implementation, Evaluation). Subjek penelitian adalah siswa kelas V SDN Oro-Oro Pule. Teknik pengumpulan data dilakukan melalui observasi, wawancara, angket, serta uji coba produk. Data dianalisis secara deskriptif kualitatif dan kuantitatif untuk mengetahui kelayakan serta efektivitas media yang dikembangkan. Hasil penelitian menunjukkan bahwa media audio visual yang dikembangkan dinilai sangat layak digunakan dalam pembelajaran PAI, baik dari aspek materi, tampilan, maupun kemudahan penggunaan. Respon guru dan siswa menunjukkan tingkat kepuasan yang tinggi karena media ini mampu menumbuhkan minat belajar, mempermudah pemahaman kisah Nabi, serta meningkatkan partisipasi aktif siswa dalam proses pembelajaran. Selain itu, penerapan media ini berdampak positif terhadap pencapaian hasil belajar, terlihat dari peningkatan nilai rata-rata siswa setelah menggunakan media. Dengan demikian, pengembangan media audio visual terbukti efektif dalam meningkatkan kualitas pembelajaran PAI, khususnya pada materi kisah Nabi Muhammad SAW membangun Kota Madinah di sekolah dasar.